2016
DOI: 10.1186/s13287-015-0272-1
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cell transplantation for multiple sclerosis: is it a clinical reality?

Abstract: Hematopoietic stem cell transplantation (HSCT) is a treatment paradigm that has long been utilized for cancers of the blood and bone marrow but has gained some traction as a treatment paradigm for multiple sclerosis (MS). Success in the treatment of patients with this approach has been reported primarily when strict inclusion criteria are imposed that have eventuated a more precise understanding of MS pathophysiology, thereby governing trial design. Moreover, enhancing the yield and purity of hematopoietic ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 51 publications
(60 reference statements)
0
18
0
Order By: Relevance
“…Although haematopoietic stem cells comprise only 0.01% of nucleated cells in the marrow, they can restore all blood lineages following myeloablation 14. The key marker in clinical practice used to predict functional engraftment is the peripheral CD34-positive cell count, with a requirement for 2–3×10 6  CD34-positive cells/kg body weight 15.…”
Section: Haemopoietic Stem Cell Collection Graft Preparation and Stomentioning
confidence: 99%
“…Although haematopoietic stem cells comprise only 0.01% of nucleated cells in the marrow, they can restore all blood lineages following myeloablation 14. The key marker in clinical practice used to predict functional engraftment is the peripheral CD34-positive cell count, with a requirement for 2–3×10 6  CD34-positive cells/kg body weight 15.…”
Section: Haemopoietic Stem Cell Collection Graft Preparation and Stomentioning
confidence: 99%
“…Hematopoietic stem cell transplantation (HSCT) has been reviewed in detail elsewhere [112][113][114][115][116]. Studies on animal models showed that strong immunosuppression followed by syngeneic bone marrow transplantation can induce long term antigen-specific tolerance [117].…”
Section: Autologous Bone Marrow Transplantationmentioning
confidence: 99%
“…The choice of the conditioning regimens (myeloablative or non-myeloablative) can impact the outcomes both in terms of efficacy and toxicity [113]. The myeloablative conditioning regimens can completely eliminate the activated immune cells before the HSCT treatment, but would expose the patients to aplasia-related complications and death [113]. The use of lymphoablative but non-myeloablative conditioning regimens would be in keeping with "the rationale of auto-HSCT […] to revive an antigen-naive immune system from the patient's HSCs" [113] whilst mitigating adverse effects such as neurotoxicity [124].…”
Section: Autologous Bone Marrow Transplantationmentioning
confidence: 99%
See 2 more Smart Citations